Perancangan User InterfaceAplikasi Persediaan dan Distribusi Bubuk Kopi Berbasis Web dengan Model SCM Pada UD. Arman Kota Padang - Arman Arman; Defiariany Defiariany; Zainul Efendy; Yani Despita Sari (IndraTech, 2021)
The purpose of this study was to design a web-based coffee powder supply and distribution application with the SCM method at UD. Arman, where UD. Arman has been facing a problem that is where the processing of inventory data and the distribution of coffee powder products become the problem of the coffee powder that distributors to characters and suppliers are still done manually. So you can know how to inventory at U.D distributors and stores. Arman must wait for confirmation first. With the problems that occur it is necessary to have a special system that can be used to manage inventory and can monitor the product inventory at each distributor and keep the merchant less. the problem faced so far is necessary to find a solution to overcome the problems that occur by designing a web-based application interface and copy book distribution application with the SCM method and building distribution-based supply chain management and supply chain management (SCM) systems at UD Arman using a methodology research using SCLD and system design tools using the UML approach. This system is built using the PHP programming language and MySQL database.Based on the results of the Black box testing, this application already has a function that is in accordance with the results of their respective functions running well. As for the usability method of the SUS method, respondents gave an average score of 72 which means that the test results obtained get a score above the average. Means the value is acceptable (acceptable) by the user. Systems designed to support employee performance and service quality to distributors and stores are included, so leaders are easy to monitor all activities and state of the coffee powder stockKeywords - Design, Supply, Distribution, SCM, UML, Web